Inflammatory response of canine gingiva to a chemical retraction agent placed at different time intervals - Asadallah Ahmadzadeh; Naim Erfani Majd; Joseph Chasteen; Azita Kaviani; Mohammad Amin Kavoosi (Wolters Kluwer Medknow Publications, 2014)
Background: Exposure of the gingival sulcus while controlling hemorrhage is prerequisites for maximizing treatment outcomes of cervical carious lesions and for obtaining quality impressions for the fabrication of indirect restorations with cervical finish lines. Gingival retraction cords saturated with different chemical agents are widely used for this purpose. The aim of this study was to investigate and compare the inflammatory potential of 15.5%ferric sulfate on connective tissue when placed at different times. Materials and Methods: All procedures were performed on three dogs under general anesthesia. Retraction cords saturated with a 15.5% ferric sulfate solution were placed into the gingival sulcus and evaluated after 3 min and 10 min of exposure to the chemical agent. Excisional biopsies of the exposed gingival tissue were then obtained at intervals of 1 h, 24 h, and 7 days. For all specimens, histology evaluation was performed using light microscopy. Data collected from the microscopic images of all tissue specimens were analyzed by using the Wilcoxon Signed Rank and Kruskal-Wallis Tests. P value less than 0.05 was considered as significant. Results: Histopathologic examination of the biopsied gingival tissue revealed that the ferric sulfate solution caused significant tissue changes at the beginning of both the 3-min and 10-min gingival exposure time (P > 0.05). However, the tissue returned to a normal histological appearance by the end of day 7 in all cases (P > 0.05). Conclusion: The results of this study revealed that the biologic effects of 15.5% ferric sulfate solution are clinically acceptable and reliable when gingival exposure times of 3 min and 10 min are used for gingival retraction.